Drainage conformation and transient response of river system in thrust segmentation of Northwest Himachal Himalaya, India. (20th February 2021) - Joshi, Neha; Kothyari, Girish Ch; Pant, Charu C.
Abstract: In the northwest Himalayan region, the ongoing out-of-sequence deformation caused emergence of Back Thrust (BT) around 43ka, which attributed the growth of anticlines parallel to the strike of major thrusts. This spatial and temporal geomorphic deformation is accompanied by coexisting river incision in the axial zone of anticlines and base-level fall along with upstream migration of knickpoints in the longitudinal river course. We used the Stream Power Incision model (SPIM) which relates the normalized steepness index (ksn ), and concavity index (θref ) with the slope (S) of longitudinal river profile as a power-law function of upstream area (A). and estimated these parameters for Beas, Soan, and Sutlej rivers to decipher the spatial distribution of deformation pattern. Using SRTM DEM and based on strike parallel variations of the ksn we identified segmented nature of the NW Himalayan thrusts. Further, the dynamics of river basins and transience along the tributaries and main stem rivers has been analyzed by Chi analysis (χ), which is attributed to geometric disequilibrium of the rivers. The results of ksn and χ analysis together suggests that the crustal shortening of NW Himalaya is caused by segmental reactivation of the thrusts. Further, investigating the change in steepness along longitudinal course aids in understanding the differential uplifts patterns in actively deforming segments of major NW Himalayan thrusts.